Oblique stagnation-point flow of ternary hybrid nanofluid towards a shrinking surface - Rozaidi, N. L.; Hafidzuddin, M. E.H.; Arifin, N. M.; Ab Ghani, A. (Lviv Polytechnic National University, 2025)
The oblique stagnation-point flow of a ternary hybrid nanofluid towards a shrinking surface is studied numerically in this paper. A similarity transformation was used to convert the governing equations into a set of ordinary differential equations, which were then solved numerically using the bvp4c solver in MATLAB software. The research, involving three different nanoparticles, provides valuable insights into their impact on the fluid dynamics and heat transfer characteristics of the system under study. The influence of the parameters S, λ and nanoparticle volume fraction on velocity and temperature profiles, local skin friction and local Nusselt number are discussed and presented in tabular and graphical forms. It is found that higher nanoparticle concentrations lead to increased resistance to flow, convection, and heat transfer rates.